Some molecular properties of 2-Hidroxyimino-1-phenylethanone thiosemicarbazone using theoretical approach - Prades-Escobar, Eliecer; Casals-Hung, Magaly; Hernández-Molina, Yennys (Revista Cubana de Química, 2017)
The optimized molecular structure, atomic charges, NBO, electronic properties, NLO of molecule 2-Hidroxyimino-1-phenylethanone thiosemicarbazone (HIPET) have been studied theoretically. The calculations were performed by Hartree-Fock (HF) and density functional theory (DFT)/B3LYP methods using 6-31G (d,p) basis set. The stability and charge delocalization of the molecule were studied by natural bond orbital (NBO). The reactivity of the compound of interest was described by HOMO–LUMO energies and global descriptors. The title compound exhibited good nonlinear optical activity and two times greater than thiosemicarcazide. Keywords: oxime-thiosemicarbazone, Hartree-Fock, density functional theory, nonlinear optical properties, reactivity descriptors.